A Critical Study on the Development of Inland Water Transport with Special Reference to the Interest Subsidy Scheme - Planning Commission (Transport Division Planning Commission Government of India, 1986)
Inland Water Transport (IWT) in India presents a cost-effective and fuel-efficient solution for transporting low-value, high-volume cargo across the country’s river networks. Despite its historical importance, IWT utilization has declined due to competition from faster transport modes and reduced navigability caused by irrigation and maintenance issues. The Seventh Five-Year Plan allocated Rs. 225.73 crores for IWT development, emphasizing modernization of vessels, establishment of integrated terminals, and designation of National Waterways. However, challenges persist, including limited scheme outreach, regulatory hurdles under the Inland Vessels Act, and uneven benefits reaching primarily industrial players rather than rural communities. The report highlights the need for legislative reforms, enhanced publicity, technological R&D, and efficient infrastructure investment to realize IWT’s full potential, thereby improving connectivity, supporting economic growth, and benefiting marginalized populations.
Planning Commission Transport Division September 1986
Keywords: Inland Water Transport; Cost-Efficiency; Navigable Waterways; Modernization; Interest Subsidy Scheme; National Waterways; Regulatory Framework; Transport Policy; Investment Plans; Bulk Cargo; Rural Connectivity; Hydrographic Surveys